An Analysis of Learning Management Based on Merdeka Belajar Curriculum in Teaching Students Writing Skill of the Eighth Grade of SMP Negeri 2 Dharma Caraka Gunungsitoli Selatan in 2023/2024 - Larosa, Fimel Rospintar Iman; Zebua, Elwin Piarawan; Harefa, Trisman; Telaumbanua, Kristof Martin Efori (Academy of Education Journal, 2024)
Writing is a crucial skill in language that enables individuals to express their thoughts and ideas. However, many of students difficulties with writing, and teachers play a significant role in aiding students to achieve their desired learning outcomes. The purpose of this study was to analyze the learning management based on Merdeka Belajar curriculum in teaching writing skill class at SMP Negeri 2 Dharma Caraka. Two English teachers and 27 students were observed through a qualitative descriptive analysis that focused on planning, implementation, and assessment. The results revealed that the learning planning was well-prepared by creating learning devices such as ATP and MA, equipped with completeness criteria. ATP provided is equipped with ten completeness components, while the MA consists of three general components. However, the MA created by the first English teacher has better completeness criteria than the module created by the second English teacher and the modified module can be developed into a learning book. Moreover, the learning implementation was conducted into three stage of learning by integrating Merdeka curriculum principles and varied teaching techniques such as lecturing, discussions, Q&A, quizzes, and PjBL. The evaluation approach consisted of diagnostic, formative, and summative assessments, demonstrating excellent learning management of the teacher. However, some students showed minor difficulties in writing, they were able to express their ideas, communicate their opinions, and improve their writing skills through the observed teacher's excellent management of the class.